COMPARATIVE STUDIES ON SYNTHESIS AND STRUCTURE OF OLD AND NEW POLYMORPHS OF DESVENLAFAXINE - AN ANTIDEPRESSANT DRUG - Khandpekar, Mahendra (Indonesian Journal of Pharmacy, 2014)
Desvenlafaxine  succinate (pristiq) is an important non-hormonal drug used in the treatment of major depressive disorder and problems associated with menopause.This article summarizes the synthesis and investigation of new polymorphic form of Desmethylvenlafaxine. The new polymorph has been compared with the old polymorph using XRD, DSC, FTIR, SEM and HPLC techniques. Three prominent reflections with higher intensities lying at 20.3, 13.1 and 15.8 have been noted in the XRD measurements for the new polymorph. Higher intensity (XRD) peaks for the new polymorph indicates good crystalline quality. FTIR spectra shows close match between the polymorphs. DSC measurements show enhanced thermal stability for the new polymorph. Higher purity is indicated by the HPLC studies.Key words: desvenlafaxine, polymorphism, structure, crystalline, purity